Oral health and quality of life in children with blood coagulation disorders and hemoglobinopathies. A cross-sectional study - Vediyera Chandroth Santhosh; Ankit Mahajan; Abhigyan Manas; Madhura Pawar; Shivangi Gupta (Journal of Family Medicine and Primary Care)
Background: Blood coagulation-associated disorders including coagulopathies have been found to affect morbidity in terms of both oral and physical health. The present study aimed to assess the oral health status and quality of life in children with blood coagulation disorders and hemoglobinopathies. Materials and Methods: This was a cross-sectional study conducted in ‘Centre for hemophilia and blood disorders’. The study group comprised of 39 children afflicted by hemophilia A, 12 children affected by hemophilia B, and 29 children having von Willebrand disease. The pediatric health-related quality of life was used for evaluating the age groups. Oral screening was performed by 2 investigators in daylight using mouth mirror and probe. Inter-examiner agreement was assessed upon 25% of studied sample using Kappa analysis and was found to be 0.89. Statistical analysis: The coded data were analyzed using the statistical software SPSS version 23.0 (IBM Corp., NY). Data entered were as frequency distribution, mean, and standard deviation. ‘Chi-square’ statistical tool was used for comparison of categorical variables. Continuous type of data was analyzed by ‘Mann–Whitney U’ test. Results and Observations: 67% of cases were brushing once daily whereas 33% had brushed their teeth twice a day. 78% of controls were brushing two times per day, and 22% were brushing their teeth one time daily. 78% of control subjects were brushing twice whereas 22% were brushing only once which was statistically significant (P = 0.04). 50% of cases had fair oral health, 30% had good, 10% were having excellent whereas 10% had poor oral health. Oral health was assessed by DMFT for permanent teeth, dmft for primary dentition, and POQL index scores. Mean ± S.D. values’ comparison was found to be statistically different (P = 0.05 each). POQL index scores were found to have statistical significance (P = 0.04) in both less than 12 and 12-16 years age groups. Conclusion: Poor oral health was found to significantly affect the general physical health and quality of life among children affected with blood coagulation disorders and coagulopathies.